Deconstructing opera for opera’s sake: an interview with Opera Queer (Argentina) - Jazmín María Tiscornia; Giselle Araceli Méndez (Transposition)
Ópera Queer is a queer lyric company that emerged in Buenos Aires, Argentina. In this interview we talk to its members, Ferni and Luchi, to know how they carry out the militancy for LGBTIQ+ rights in relation to opera.